Vietnamocasia, a new genus from Central Vietnam belonging to the Alocasia-Colocasia clade (Araceae) - Ly, Ngoc-Sam; Wong, Sin Yeng; Haevermans, Thomas; Nguyen, Van Du; Boyce, P.C (Magnolia Press, 2017)
Vietnamocasia, a new monotypic aroid genus in the Alocasia-Colocasia clade, is described with the type species, Vietnamocasia dauae. Vietnamocasia is distinguished by possessing free individual staminate flowers, lacking expanded synconnectives, and having nodding inflorescences. Vegetatively Vietnamocasia is reminiscent of species of the distantly closely related Alocasia Cuprea Group, although Vietnamocasia is so far only known from the type locality in Central Vietnam, over 1200 km NE from the nearest representative of the Alocasia Cuprea Group. The phylogenetic analyses of Vietnamocasia dauae together with representative taxa from all genera of the Alocasia-Colocasia clade recovered Vietnamocasia as a strongly supported clade sister to Alocasia, together nested in a clade to which Leucocasia is a sister taxon. Vietnamocasia dauae is illustrated from living plants and with a line drawing. A key to all genera of Alocasia-Colocasia clade is included.